Peculiarities of qualification of crimes in the field of computer information and counteraction to them - I. A. Efremova (Правоприменение)
The subject of the study is the specifics of the qualification of crimes in the field of computer information and measures to counter them. The purpose of the study is to examine the specifics of the qualification of crimes in the field of computer information and to develop effective measures to counter them. Research methodology. Along with the universal method of cognition, general scientific and private scientific methods were used: first of all, the statistical method, system-structural analysis, analytical research. This made it possible to comprehensively investigate the specifics of the qualification of crimes in the field of computer information and identify measures to counter them. Scientific results of the study. It has been established that recently there has been an increase in crimes committed in the field of computer information and (or) using information and telecommunication networks. In 2023, the share increased from 26.5% to 34.8% compared to the previous year. More than half of such crimes (50.6%) belong to the categories of grave and especially grave. It is determined that criminal liability for crimes committed in the field of computer information is established in Chapter 28 of the Criminal Code of the Russian Federation "Crimes in the field of computer information", for crimes committed using information and telecommunication networks - in art. 105; 110; 110.1; 110.2; 111; 112; 115; 116; 117; 119; 126; 127; 127.2; 128.1; 133; 137; 151.2; 159.6; 171.2; 185.3; 205.2; 222; 222.1; 228.1; 230; 238.1; 242; 242.1; 242.2; 245; 258.1; 260.1; 280; 280.1; 280.4; 282; 354.1 The Criminal Code of the Russian Federation, containing a qualifying The attribute is an information and telecommunication network. The classification of this feature as qualifying is based on the degree of public danger of the crime. But there is a varying degree of public danger of these acts. In some formations, the commission of a crime using information and telecommunication networks is a qualified type (art. 110, 110.2, 128.1, 151.2, 205.2, 228.1, 230, 242.1, 242.2, 245, 258.1, 260.1, 280, 280.1, 280.4 of the Criminal Code of the Russian Federation), in others – especially qualified (art. 110.1, 133, 137, 222, 222.1, 242 159.6, 171.2, 185.3, 238.1 of the Criminal Code of the Russian Federation). It is noted that this feature raises questions when qualifying, for example, when identifying an organized group that commits criminal acts using information and telecommunications networks, including the Internet; distinguishing from other crimes. As measures to counteract crimes committed in the field of computer information and (or) using information and telecommunication networks, including the Internet, it is proposed: to develop a concept of economic development to overcome poverty; to instill a culture of using digital technologies, to form positive value orientations; to develop a Concept of crime prevention, in which it is necessary to devote a separate section on these criminal acts; develop a national plan to counter these crimes; to increase the equipment of law enforcement agencies; to create specialized units for countering cybercrime in the structure of the Ministry of Internal Affairs of the Russian Federation, etc. Conclusions about the achievement of the purpose of this study. In the conducted research, the problems of qualification of crimes in the field of computer information are identified and counteraction measures are proposed.